ANALISIS VARIASI KRITERIA AWAL WAKTU SUBUH DI INDONESIA TERHADAP PELAKSANAAN IBADAH SALAT DAN PUASA: ANALISIS VARIASI KRITERIA AWAL WAKTU SUBUH DI INDONESIA TERHADAP PELAKSANAAN IBADAH SALAT DAN PUASA - Wahidin, Nurul Wasilah; Fatmawati; Nur Hijriah (ELFALAKY: Jurnal Ilmu Falak, 2023)
The problems with the implementation of prayer and fasting in Indonesia are varied, which refers to the timetable for prayer and imsak which is issued periodically at the beginning of each Islamic month in an area, especially at dawn, which shows differences with various criteria for the height of the sun angle. This has become urgent and has been widely analyzed by astronomers and astronomers because it is a reference for the community in carrying out prayers and fasting. The type of research used is Library Research with a descriptive qualitative approach. This research is to identify and analyze the various early dawn criteria in Indonesia by taking samples of prayer time schedules published in print and online media and their implementation. The results of various variations on the early dawn criteria were published by the Ministry of Religion and several Islamic organizations and institutions in Indonesia. The criteria for the initial dawn time of the Ministry of Religion and NU are -20º, Muhammadiyah is and Wahdah Islamiyah is -18º, and the Fazilet Calendar is -19º with the addition of tamkin.